Analysing the meaning of Dataran Pahlawan as a ‘new’ public space in a historic city of Melaka - Harun, Nor Zalina; Zakariya, Khalilah; Mansor, Mazlina (2015)
Previous researches have made critical contributions to the understanding of the significance of place to people. Despite the numerous studies over the last thirty years, the study on the relationship between place and place meaning remains unclear. In this regards, this study aims to explore one spectrum of people’s place experience to reveal an understanding of place meaning as it is a complex and multi-faceted phenomenon that comprises of people’s emotional relationships to place. Another concern of the study is to identify the importance of public space in historical cities. Firstly, the paper reviews the relevant literature on place and place meaning, while disparate and integrating concepts of it are encountered through semi-structured interviews with users of public space (n=40) in Melaka (a UNESCO world listed heritage city). The study folds the meaning of one long existed public space that had undergone a series of change, which is locally known as Dataran Pahlawan. Evolved from a seaside esplanade originally known as Padang Pahlawan, space was gradually transformed in term of functions and physical appearance. The study provided evidence on people’s experience of the place. Among others, there was an emotional delight arising from the experience of Dataran Pahlawan as users’ favourite public space. Hence, in a broad context it shows that users have a strong sense of attachment to the public space. The changes and the loss of Padang Pahlawan as a memorable public place have not weakened the place identity of the city and its place meaning. To the residents, the Dataran Pahlawan and its surrounding still contributed a panoramic experience and urban enjoyment. There are indeed elements that are commonly recognized with pleasure and care by the users, in which the study shows that the physical changes in some way modified people’s will and awareness towards urban conservation. The study also corroborates additional benefits of Dataran Pahlawan, which are obtained through the very form and nature of the city. It is suggested that the area and it's surrounding convey various architectural meanings such as civic and ceremonial ground, a square, a district, a landmark and a node. It is a vision that results of mapping the meaning of the public space may determine its significance and values that contribute to the evocation of place identity in the Malaysian urban area.